Characterization of the evolution of 2219-T87 aluminum as a function of the friction stir welding process. (January 2021) - Anderson-Wedge, K.; Stubblefield, G.; Zhu, N.; Long, B.; Daniewicz, S.R.; Allison, P.; Sowards, J.; Rodriguez, O.; Amaro, R.
Highlights: The availability of strengthening phase influences FCG behavior of the FSW material. Changes in FCG rate within weld are attributed to PICC and/or RICC, not residual stress. Microstructural evolution influences FCG rate, microhardness, and grain morphology. Abstract: The aluminum-copper alloy AA2219 is commonly joined by friction stir welding (FSW). The strengthening Al2 Cu phases are affected by the temperatures produced as a function of the FSW process. This work characterizes the effect of FSW on the fatigue crack growth and fracture response of the of AA2219-T87. Specifically, the virgin material's microhardness, strength, and θ-phase evolution are studied as a function of time and temperature. This data is compared to the microhardness resulting in the stir zone, thermo-mechanically affected zone (TMAZ), heat affected zone (HAZ), and base material. Furthermore, the residual stresses produced by the FSW process are quantified.